Ovarian Hyperstimulation Syndrome in a Patient with Hypogonadotropic Hypogonadism - Sarıkaya, Esma; Eryılmaz, Ozlem; Moraloglu, Ozlem; Yılmaz, Saynur; Gulerman, Cavidan (Fırat University, 2012)
Traditionally, women with hypogonadotropic hypogonadism (HH) were considered to be at lower risk for the development of ovarian hyperstimula-tion syndrome (OHSS), although they usually required higher doses of gonadotrophins and longer periods of treatment. However this case emphasize that OHSS can be seen in patients with HH especially in a group of patients with the ultrasound findings of PCO.

Daha uzun tedavi periyodu ve daha yüksek doz gonadotropin kullanımı gerekse de hipogonadotropik hipogonadizm (HH) olan hastalarda ovarian hiperstimulasyon sendromu (OHSS) gelişme riskinin daha düşük olduğu bilinen bir gerçektir. Ancak bu vaka HH olan ve özellikle polikistik over ultrason bulgusu taşıyan hastalarda OHSS gelişebileceğini vurgulamaktadır.
Hipogonadotropik Hipogonadizm Olan Bir Hastada Ovarian Hiperstimulasyon Sendromu